Study of Effect Changing the Blade Shape and Lift Angles on Horizontal Wind Turbine - Ichsan Astanto; Fatahul Arifin; Yohandri Bow; Sirajuddin (International Journal of Research in Vocational Studies (IJRVOCAS), 2022)
The lack of energy commodities such as coal and petroleum makes the cost of these commodities soar. This event shows how much countries in the world are still very dependent on fossil fuels, and it is fitting that the transition to new renewable energy can be realized soon, low emission and environmentally friendly energy is the hope in the future. Indonesia has a supply of renewable energy sources that are abundant is a great force for this clean energy revolution. The momentum of the presence of the first wind farm in Indonesia operating in Mattirotasi Village, Sidrap Regency, Central Sulawesi in Indonesia with a wind power plant capacity (PLTB) of 75 MW is positive evidence that the government is starting to pay more attention to the development of renewable energy technology in Indonesia. Turbine technology that is able to optimize wind speed in Indonesia must be the answer so that this energy is more useful.  In this study, the idea for an experimental analysis of "Study of the Effect of Blade Shape Change and Lift Angle on Horizontal Wind Tubin using Nvis 6009 Experimentation with Solar and Wind Energy props. The Nvis 6009 is a prop used by vocational schools to understand the concept of a DC power plant based on solar and wind energy. To optimize low wind speed, on Nvis 6009 horizontal axis wind turbine (HAWT) with different type 3 Blade and changes in lift angle, so that we can know the effect of the resulting voltage change, so that we can know the effect of the resulting voltage change. Simple illustrations using the Solidworks application are done as validation of the results of previous research and to obtain preliminary data of research experiments. The final results of the test on Type Blade II obtained maximum data at a Blade angle of 13 ° with a wind speed of 3.9 m / s, Blade Rotation 2587 Rpm produces a voltage of 2.8 V.